Effect of Diffusion on Photo-Induced Excited-State Energy Transfer between Fluorescent Semiconducting Molecules: Tris-(8-hydroxyquinoline) Aluminum and 6,13-Bis (Triisopropylsilylethynyl) Pentacene - Bisht H.; Singh A.P.; Jit S.; Pokharia S.; Mishra H. (My University, 2025)
In the present work, the effect of diffusion on photo-induced excitation energy transfer between fluorescent organic semiconducting molecules tris-(8-hydroxyquinoline) aluminum (AlQ3, n-type donor) and 6,13-bis (triisopropylsilylethynyl) pentacene (TIPS-P, p-type acceptor) at a concentration range of 10-4to 10-6M in chloroform solution was studied by steady-state and time-domain fluorescence measurements. The donor-donor interaction strength is significantly weaker than the donor-acceptor strength (the ratio of donor-donor to donor-acceptor interaction strengths is 1.55 × 103) in chloroform solution. Considerable overlap between donor emission and acceptor absorption and high interaction parameters favors direct Förster energy transfer and exciplex (D*A) formation. Excitation energy migration does not take place between donor molecules. However, material diffusion appears to influence the donor decay dynamics by forming charge-transfer exciplex complexes and modulating the excitation energy transfer rate from the metal-to-ligand charge-transfer (MLCT) state of the donor to vibronic states of the acceptor at a low acceptor concentration. At high acceptor concentrations, energy transfer from the excited donor to acceptor occurs through the exchange mechanism along with Förster long-range dipole-dipole interactions, and the corresponding critical transfer distance is found to be ∼42 Å. A blue-shift in AlQ3emission, a red-shift in the 0-0 vibronic peak of TIPS-P, and quenching of exciplex decay following Stern-Volmer quenching are observed, with the increase in acceptor concentration. No evidence of excimer formation is observed in acceptor molecules. © 2021 American Chemical Society